Machine Learning Algorithms: Optimizing Efficiency in AI Applications - Rasiklal Yadav, Balkrishna (International Journal of Engineering and Management Research, 2024)
Machine learning (ML) is an AI technology that creates programs and data models that can perform tasks without being instructed. It has three major types: guided learning, uncontrolled learning, and reinforcement learning. ML is essential for big projects like real-time decision-making systems and self-driving cars, robots, and drones. It improves AI systems by making it easier to create models, work with data, and run algorithms. ML algorithms have different types of learning, require different amounts of data and training times, and can be improved by tuning hyperparameters. Techniques like feature selection, dimensionality reduction, model editing, and compression can improve performance and accuracy in various fields. In the real world, making AI apps more efficient can lead to more options, lower prices, and faster processing. Key techniques like model compression, transfer learning, and edge computing are needed to achieve these goals.